"Evidence‐Based Interventional Pain Medicine According to Clinical Diagnoses": Update 2018. Issue 6 (2nd May 2019) - Huygen, Frank; Kallewaard, Jan Willem; van Tulder, Maurits; Van Boxem, Koen; Vissers, Kris; van Kleef, Maarten; Van Zundert, Jan
Abstract: Introduction: Between 2009 and 2011 a series of 26 articles on evidence‐based medicine for interventional pain medicine according to clinical diagnoses were published. The high number of publications since the last literature search justified an update. Methods: For the update an independent 3rd party, specialized in systematic reviews was asked in 2015 to perform the literature search and summarize relevant evidence using Cochrane and GRADE methodology to compile guidelines on interventional pain management. The guideline committee reviewed the information and made a last update on March 1st 2018. The information from new studies published after the research performed by the 3th party and additional observational studies was used to incorporate other factors such as side effects and complications, invasiveness, costs and ethical factors, which influence the ultimate recommendations. Results: For the different indications a total of 113 interventions were evaluated. Twenty‐seven (24%) interventions were new compared to the previous guidelines and the recommendation changed for only 3 (2.6%) of the interventions. Discussion: This article summarizes the evolution of the quality of evidence and the strength of recommendations for the interventional pain treatment options for 28 clinical pain diagnoses.